Down-regulation of SNX1 predicts poor prognosis and contributes to drug resistance in colorectal cancer - Bian, Zehua; Feng, Yuyang; Xue, Yao; Hu, Yaling; Wang, Qifeng; Zhou, Leyuan; Liu, Zhihui; Zhang, Jiwei; Yin, Yuan; Gu, Bing; Huang, Zhaohui (Tumor biology, 2016)
As a potential tumor suppressor, the detailed clinical application value of sorting nexin 1 (SNX1) has not been elucidated in colorectal cancer (CRC). The aim of the present study was to evaluate the expression of SNX1 in CRC tissues and to determine its correlation with clinicopathologic characteristics and its impact on patient’s prognosis. We detected the expression of SNX1 mRNA in 72 CRC patients and SNX1 protein in 237 CRC patients by real-time polymerase chain reaction (RT-PCR) and immunohistochemical staining, respectively. Relationship between the expression of SNX1 and various clinicopathological features in these patients was evaluated. Both the mRNA and protein expression of SNX1 were remarkably decreased in CRC tissues compared with paired non-cancerous tissues, and the down-regulation of SNX1 protein was strongly associated with poor differentiation and poor overall survival (OS) rate of CRC patients. Ectopic SNX1 expression repressed CRC cell growth and promoted tumor sensitivity to most commonly used chemotherapeutic drugs (oxaliplatin and 5-Fluorouracil). In conclusion, overexpression of SNX1 may serve as a new therapeutic strategy for CRC.